Black Byronism. Issue 1 (June 2017) - Sandler, Matt
Abstract : This essay makes a case for Byron's transformative influence on the emergence of African American literature. I begin with a discussion of the widespread citation of some lines from Childe Harold's Pilgrimage in canonical works of nineteenth-century African American literature. I then focus on love lyrics and epic poetry from the antebellum decades through the Reconstruction and its aftermath, when Black masculinity came under renewed surveillance and when Byron's reputation was increasingly marred by scandal. Throughout, I argue that nineteenth-century African American writers drew on Byron to mount critiques of slavery as a kinship regime, to displace the moral coordinates of conventional representations of Blackness, to avoid the pressures and pitfalls of the marketplace for slave narratives, and to mark their poetic deviance from within the tradition of revolutionary liberalism.